2017
DOI: 10.1038/s41559-017-0154
|View full text |Cite
|
Sign up to set email alerts
|

Sperm and sex peptide stimulate aggression in female Drosophila

Abstract: Introductory paragraphFemale aggression towards other females is associated with reproduction in many taxa, and traditionally thought to be related to the protection or provisioning of offspring, such as through increased resource acquisition. However, the underlying reproductive factors causing aggressive behaviour in females remain unknown. Here we show that female aggression in the fruit fly Drosophila melanogaster is strongly stimulated by the receipt of sperm at mating, and in part by an associated semina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
116
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(131 citation statements)
references
References 62 publications
11
116
2
Order By: Relevance
“…We tested whether mating status and larval density influence female competition in D. melanogaster . Consistent with previous findings (Bath et al, ), contest duration was strongly influenced by mating status, whereby pairs of mated females fought for longer than mixed pairs, or pairs with two virgin females. However, we found that high density larval environments strongly exacerbated the difference in contest duration between mated and virgin female pairs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We tested whether mating status and larval density influence female competition in D. melanogaster . Consistent with previous findings (Bath et al, ), contest duration was strongly influenced by mating status, whereby pairs of mated females fought for longer than mixed pairs, or pairs with two virgin females. However, we found that high density larval environments strongly exacerbated the difference in contest duration between mated and virgin female pairs.…”
Section: Discussionsupporting
confidence: 91%
“…We previously demonstrated that ejaculate components transferred at mating increase the duration of female aggression in female D. melanogaster but detected no effect of mating on fighting success (Bath et al, 2017). Crucially, our previous work was conducted on females all raised in benign, resource-rich and low density developmental environments.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Females often demonstrate different patterns of aggressive behaviours than males (Nilsen et al., ), and competitive behaviour in females may be more influenced by the value of the resource than competition among males (Cain & Langmore, ; Draud, Macias‐Ordonez, Verga, & Itzkowitz, ; Tibbetts, ). Furthermore, female aggression increases after mating (Bath et al., ), which may have accounted for higher aggression in females compared to males, as it is unlikely any females were virgins at the time of our trials.…”
Section: Discussionmentioning
confidence: 98%
“…And what better way to dissect this than with the powerful model system, Drosophila melanogaster , whose aggressive behaviour was first described over 100 years ago by Sturtevant 2 . Writing in Nature Ecology & Evolution , Bath et al 3 show that the extended duration of female aggression in fruit flies is caused by receipt of sperm and, in part, by receipt of a seminal fluid protein, known as the sex peptide (SP), during mating. Therefore, their results show that aggressive behaviours in one sex can be influenced significantly by chemical messages from the other, and open up many questions regarding the function and adaptive value of female aggressive behaviour.…”
mentioning
confidence: 99%